Supply Chain Transformation : Practical Roadmap to Best Practice Results. - Sherman, Richard (Wiley, 2012)
Achieve best practices in supply chain management Much is being written about global supply chain and sourcing options emerging in today's marketplace. Transforming supply chain management to achieve operations excellence is a mandate for many companies globally. Supply Chain Transformation walks you through this potentially difficult process and gets you started on the journey. Much more than just a how-to book, it's a why-to book that is as compelling for any business person as it is for supply chain management professionals. This book provides an invaluable road map to companies looking to.- Resumé vydavatel